SPECIFIC STRUCTURE OF THE NORMAL RAT GASTRIC FUNDUS WALL - Yachmin, А.І.; Vilkhova, O.V.; Boruta, N.V.; Bilash, S.M.; Yeroshenko, G.А.; Skotarenko, T.A.; Bilash, V.P.; Kramarenko, D.R. (World of Medicine and Biology, 2020)
As a result of a comprehensive study, it was determined that the wall of the fundus of the stomach of rats according to the basic principles of structural organization corresponds to humans and can be used as an experimental model to study the effects of exogenous factors. By means of morphometric research the basic metric indicators of a wall of fundal department of a rats’ stomach and histotopographic features of own glands are established.
Keywords: fundus of the stomach; wall; own glands; morphometry